2014
DOI: 10.1111/1751-7915.12116
|View full text |Cite
|
Sign up to set email alerts
|

Activation and identification of five clusters for secondary metabolites in Streptomyces albusJ1074

Abstract: Streptomyces albus J1074 is a streptomycete strain widely used as a host for expression of secondary metabolite gene clusters. Bioinformatic analysis of the genome of this organism predicts the presence of 27 gene clusters for secondary metabolites. We have used three different strategies for the activation of some of these silent/cryptic gene clusters in S. albus J1074: two hybrid polyketide-non-ribosomal peptides (PK-NRP) (antimycin and 6-epi-alteramides), a type I PK (candicidin), a non-ribosomal peptides (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
185
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(191 citation statements)
references
References 72 publications
5
185
0
1
Order By: Relevance
“…Furthermore, the compound isolated from S. viridochromogenes was found to be a novel pigmented PK produced from an otherwise silent BGC of the type II PKS. Although this activation strategy bears striking similarity to a technique previously reported for the activation of five gene clusters in S. albus J1074, [52] the incentive to use the CRISPR-Cas9 system is the increased efficiency of HRs, presenting an improved method for genetic manipulation of strains suffering from the low efficiency of natural recombination.…”
Section: Molecular Tools For Streptomycetes Engineeringmentioning
confidence: 90%
“…Furthermore, the compound isolated from S. viridochromogenes was found to be a novel pigmented PK produced from an otherwise silent BGC of the type II PKS. Although this activation strategy bears striking similarity to a technique previously reported for the activation of five gene clusters in S. albus J1074, [52] the incentive to use the CRISPR-Cas9 system is the increased efficiency of HRs, presenting an improved method for genetic manipulation of strains suffering from the low efficiency of natural recombination.…”
Section: Molecular Tools For Streptomycetes Engineeringmentioning
confidence: 90%
“…The production of a variety of antibiotics is regulated by different regulatory mechanisms in streptomycetes 13,14,[17][18][19] and it is essential to choose a wide range of media for their production. 15 Because the electrically attached Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…Genetically modified streptomycetes have unleashed the production of many new biologically active compounds. 13,14,[17][18][19] Nevertheless, the rate of novel compound discovery from terrestrial microorganisms has recently decreased significantly. 20 Over the past three decades, marine environments have continued to supply a number of novel actinomycetes and bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial genome sequencing is also contributing to discovery of new polyenes and to a more complete understanding of their biosynthesis. Candicidin is frequently re-isolated and its biosynthetic gene cluster appears in several genomes (Jorgensen et al, 2009;Seipke et al, 2011b;Olano et al, 2014;Tang et al, 2015;Komaki et al, 2015;Liu et al, 2015a). Since the sequencing of the nystatin biosynthetic genes in S. noursei (Brautaset et al, 2000), at least three other closely related clusters have been found (Kim et al, 2009;Barke et al, 2012;Cui et al, 2015).…”
Section: Genes For Polyene Macrolide Biosynthesismentioning
confidence: 99%